Pelatihan dan Desain Bahasa Visual Pengemasan pada Produk Farmasi Berbasis Bahan Alam di SMK Sentosa Dharma Bojonegoro - Abdul Basith; Akhmad Al-Bari; Ria Indah Kusuma Pitaloka; Yani' Qoriati (Abdibaraya, 2026)
Packaging for natural-ingredient-based pharmaceutical products serves not only to protect the product but also as a communication medium that can enhance the product’s appeal and market value. However, students’ knowledge and skills in designing packaging's visual language remain limited. This community service activity aims to improve students' understanding and skills at SMK Sentosa Dharma Bojonegoro in designing the visual language of packaging for natural-ingredient-based pharmaceutical products. The methods used included counseling, training, packaging design practice, and guidance on product label creation. There were 35 participants in the activity, all of whom were students in the pharmacy program. Evaluation was conducted using pre-test and post-test instruments as well as an assessment of the packaging design results. The results of the activity showed an increase in participants' average knowledge score from 58.4 on the pre-test to 84.7 on the post-test, representing a 45.0% increase. Additionally, the packaging design assessment results showed an average score of 86.2 (good category), with 88.6% of participants able to arrange visual identity elements, product information, and visual communication in accordance with pharmaceutical packaging design principles. The satisfaction survey results showed that 91.4% of participants reported that the training was very beneficial in improving their product packaging design skills. This activity proved effective in enhancing students’ competencies in designing informative, attractive, and economically valuable.